Holografski princip - Dominko Kobilica, Natan (Matrika, 2022)
An intuition for the holographic principle is given. As black hole thermodynamics is a prerequisite, the greater portion of the paper is spent expounding the analogy between thermodynamical quantities and quantities describing black holes. The analogy between equations describing black holes and the laws of thermodynamics is shown and then some interesting consequences are discussed, one of which is the spherical entropy bound. The relation between entropy and information leads to the holographic principle.
Keywords: black holes; črne luknje; holografski princip; holographic principles; termodinamika; thermodynamics